The Influence of the Project Based Learning (PjBL) Learning Model on the Cognitive Achievement of Mathematics of Junior High School Students at SLBN 3 Denpasar - Wiadnyana, I Gusti Agung Gede; Sumandya, I. W.; Dianariska, D. A. Dwipa (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2026)
This study investigates the effectiveness of the Project-Based Learning (PjBL) paradigm in enhancing mathematical cognitive outcomes within a special education context. The primary motivation for this research is the prevalent low conceptual understanding of mathematics among students with special needs, often attributed to overly abstract instructional methods. Employing a quasi-experimental approach with a non-equivalent control group design, the study involved junior high school students at SLBN 3 Denpasar. Data were systematically collected using validated learning outcome instruments and analyzed through t-test statistics and effect size calculations. Empirical findings confirm that while the statistical significance value stood at 0.192, the obtained effect size coefficient of 0.81 indicates a substantial practical impact. This suggests that integrating project-based activities facilitates more concrete mathematical material assimilation compared to conventional methods. PjBL proved to provide a positive stimulus for students' knowledge retention; hence, this model is highly recommended as an alternative pedagogical strategy for teachers in special education schools. In conclusion, utilizing projects in instruction effectively bridges learning barriers for students with disabilities in comprehending numerical and spatial logic.